Islamic Higher Education's Internationalization of Islamic Studies: Revitalization or New Trend? - Sriharini; Ahmad Izudin (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2022)
Digitalization has had the greatest impact not only on the economic, social, cultural, and technological sectors, but also on the education sector. The higher level of Islamic education can be a part of its generalization. Otherwise, this article aims to explore the challenges of the period in the Revolution 5.0 era and its implications for Islamic higher education, particularly at the UIN Sunan Kalijaga. Is a lecturer still required if students were a part of the industrial revolution while the educational system was rapidly expanding? Furthermore, how is the lecturer going to prepare for the challenge? The phenomenology approach was used in this study. Based on the observation and the interview, data is analyzed to form an interpretation. According to the findings of the research, UIN Sunan Kalijaga has prepared to face the challenges of the Society 5.0 era, but the institution has not. Moreover, the institution hasn’t yet come out of the digital era; there is still much that needs to be done. For example, the systems of e-budgeting, e-public service, and e-governance haven't been formed. The conditions were constrained by a data system that requires substantial funds. The problems' recommendations are to establish an integration system for document capture and information management, to expand the knowledge foundation based on research and development, and to expand adaptive by human resources.